Tinjauan Filosofis Hukum Islam Terhadap Tradisi Menggendong Ayam Bagi Mempelai Wanita Ketika Walimatul Al-Ursy di Nagari Sontang Cubadak Kecamatan Padang Gelugur - Septi, Septi Irawani; Adra, Adrayani (Hakamain: Journal of Sharia and Law Studies, 2022)
There is a custom in Nagari Sontang Cubadak trying to hold a chicken at the time of walimatul al-ursy for the bride, what is behind the tradition so that the chicken is made part of the custom in the process of walimatul al-ursy. Therefore, this research is focused on how the philosophical review of Islamic law on the tradition of carrying chickens for the bride when walimatul al-ursy in Nagari Sontang Cubadak. From the results of the research that the author did, the authors concluded that the tradition of manggendong chicken at the time of walimatul al-ursy for the bride in Nagari Sontang Cubadak in the philosophical review of Islamic law there are benefits or benefits, namely the existence of mental training as well as non-formal education for the maintenance of offspring. it is included in the maqashid shari'ah, namely hifz nasab (maintaining offspring), besides that there is anticipation for the bride and groom from indigenous peoples if the bride and groom in living their domestic life face economic difficulties, as a way out of this problem is there are chickens that have almost laying eggs that were carried when walimatul ursy. The goodness or benefits that exist in carrying out the tradition of carrying chickens in fiqh literature are known as maslahah.